Effect of Seaweed-Based Biostimulants on Growth and Development of Hydrangea paniculata under Continuous or Periodic Drought Stress - Paulien De Clercq; Els Pauwels; Seppe Top; Kathy Steppe; Marie-Christine Van Labeke (Horticulturae, 2023)
To adapt to climate change and water scarcity during dry, hot summers, more sustainable, or even deficit, irrigation is required in the ornamental sector, as it uses large amounts of water to sustain high-value crop production. Biostimulants, especially seaweed extracts, could offer a sustainable solution against drought stress as they are known to increase plant tolerance to abiotic stress. The effect of four seaweed extracts based on Ascophyllum nodosum, Soliera chordalis, Ecklonia maxima, and Saccharina latissima and one microbial biostimulant were tested on container-grown Hydrangea paniculata under drought stress conditions for two years. During the first trial year, in 2019, overall irrigation was reduced by 20%. In 2021, plants were subjected to repeated drying and wetting cycles. In general, less irrigation, and thus a lower substrate moisture content, reduced stomatal conductance, biomass production, and root development, but increased plant compactness. The biostimulants showed minor effects, but these were not observed in both experiments. Treatment with the A. nodosum extract resulted in longer branches and more biomass under deficit irrigation but tended to accelerate flowering when repeated drying and wetting cycles were applied. The E. maxima extract negatively affected the branching of Hydrangea under repeated drying and wetting cycles.